2019
DOI: 10.1002/mame.201900433
|View full text |Cite
|
Sign up to set email alerts
|

A Ferroconcrete‐Like All‐Organic Nanocomposite Exhibiting Improved Mechanical Property, High Breakdown Strength, and High Energy Efficiency

Abstract: Polymer‐based nanocomposite dielectrics with high energy storage capacity are crucial enablers for numerous applications in modern electronic and electrical industries. The energy density of parallel plate capacitors is determined by breakdown strength and dielectric permittivity of the inner dielectrics. Poly(vinylidene fluoride‐trifluoroethylene‐chlorofluoroethylene) (P(VDF‐TrFE‐CFE)), with the highest permittivity among all the dielectric polymers, is a promising candidate for high energy density capacitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The electrical breakdown strength is also an essential property of dielectric materials. Therefore, we tested the electrical breakdown performance of various PASS films and used the two‐parameter Weibull distribution function 49–53 to analyze the measured breakdown strength dat. Weibull distribution is often used in reliability evaluation to analyze the probability of material breakdown under a certain electric field strength or failure in a certain time.…”
Section: Resultsmentioning
confidence: 99%
“…The electrical breakdown strength is also an essential property of dielectric materials. Therefore, we tested the electrical breakdown performance of various PASS films and used the two‐parameter Weibull distribution function 49–53 to analyze the measured breakdown strength dat. Weibull distribution is often used in reliability evaluation to analyze the probability of material breakdown under a certain electric field strength or failure in a certain time.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of electrospinning and hot-pressing technology provides a new method for optimizing the energy density and breakdown strength of composite materials, allowing for the investigation of the relationship between the structure and properties of composites. Reprinted with permission from [132]. Copyright (2019), Wiley.…”
Section: Linear/nonlinear Polymer Fillingmentioning
confidence: 99%
“…The breakdown strength of P(VDF-TrFE-CFE)/PSF was shown to initially increase and then decrease with increasing PSF content. As a result, nanocomposites containing 30 vol% PSF achieved a high Weibull breakdown strength of 485 MV/m, more than 50% higher than the neat terpolymer (~320 MV/m) ( Figure 13 b,c) [ 132 ].…”
Section: Linear/nonlinear Polymer Dielectricsmentioning
confidence: 99%
See 1 more Smart Citation
“…ferroconcrete‐like structure, promising for high energy density capacitor design. In previous research [42], we found that with proper design, this structure could bring about significantly improved mechanical property and enhanced breakdown strength. Herein, linear dielectric polymethyl methacrylate (PMMA) is chosen as the matrix, since its intrinsic high breakdown strength and high discharged energy efficiency.…”
Section: Introductionmentioning
confidence: 99%